The new steroidal glycosides from the aerial parts of Lepidogrammitis drymoglossoides. Issue 9 (1st September 2016) - Wei, Hua; Jiang, Hai; Liu, Zhu-Xiang; Li, Gui; Long, Hua; He, Jian-Wu; Chen, Gong-Xi; Yang, Jun-Shan; Ma, Guo-Xu
Abstract: Two new steroidal glycosides ponasteroside C (1 ) and ponasteroside D (2 ) were isolated from the aerial parts of Lepidogrammitis drymoglossoides . Their structures were elucidated by various spectroscopic techniques (IR, HRESIMS, 1D and 2D NMR). All compounds were evaluated for their cytotoxicity against HeLa and HCT-8 cell lines, and compounds1 and2 showed mild activity against all the test cell lines.